Mistreatment by Patients: An Analysis of the Patient-related Social Stressors among Slovenian Healthcare Workers - Kozjek, Tatjana (Zdr Varst, 2021)
INTRODUCTION: Healthcare workers (HCWs) are often exposed to mistreatment by patients, which has negative effects on both staff and institutions. To take appropriate action to help HCWs in this context, patient-related social stressors (PSS) should be explored. The purpose of the research was to identify the most pronounced patient behaviour contributing to the social stress (SS) of HCWs, and compare PSS between different HCWs and different types of healthcare institutions. METHODS: 750 HCWs from Slovenian public health centres and hospitals participated in the online survey. Although the non-probability sampling was used, the sample was representative according to gender and HCW type (doctors, nurses and other HCWs). RESULTS: The results show that the most pronounced patient behaviour contributing to the SS of HCWs are attitudes and behaviour of patients that are challenging in terms of what is – from the HCWs’ point of view – considered as acceptable and reasonable (disproportionate patient expectations), and unpleasant, humourless, and hostile patients. HCWs in primary institutions meet less verbally aggressive and unpleasant patients than in tertiary ones. Although among all HCWs less educated ones are more exposed to inappropriate behaviour, doctors are those HCWs who experience more inappropriate behaviour. CONCLUSION: Managers should enable HCWs to get comprehensive patient service training, oriented towards improving relationship management and patient-HCW relationships.